Interpersonal conflict from a younger point of view: Exploring the perspectives of children - Hale, C.L.; Farley-Lucas, B.; Tardy, R.W. (International Journal of Qualitative Studies in Education, 1996)
This study breaks from traditional adult-centered models of interpersonal conflict by privileging children’s experiences. As part of an assessment for establishing a school-based peer mediation program, focus group interviews were conducted with second graders through high school students. Analysis focuses on the sites (causes), signs, and aftermath (or responses) of conflict. Children’s impressions regarding fairness and gender differences are also addressed. With respect to the sites and signs of conflict, the main themes that were found include conflict as a product of the spoken word and conflict as a dirty look. Additionally, a symbolic representation of these intrusions emerged in the metaphor of conflict as an explosion. Analysis of the children's discussions concerning the aftermath of conflicts revealed four general themes: confronting, seeking involvement of third parties, ignoring others, and treating others with kindness. Differences in the children’s perceptions of gender-based differences are explored as are their perceptions of the construct of “fairness” and its associated dictates in favor of equality of treatment, struggles with inferiority/superiority, and expression of conflict as a betrayal. © 1996, Taylor & Francis Group, LLC. All rights reserved.
4 citations (Crossref) [2023-10-31]
Keywords: dept.com